Economic growth and employment: Regional disparities in the EU - Isidro Frias; M. Emilia Vazquez; Ana Iglesias (European Regional Science Association (ERSA), 1998)
One of the main problems of the European countries is their small capacity to generate employment. This is an important point because of the social and human problems that it produces, which are more serious in the case of the peripheral regions. In this paper, we make a comparative analysis of employment and economic growth among the EU and the main OECD countries. We study the reasons of the more reduced rates of employment in several EU countries in relation to USA and Japan. Then, we analyze the generation of employment in the European regions, specially in the peripheral ones which are the most affected by unemployment.
Keywords: 330